Tras el año Mantegna. Referencias, puntualizaciones, balances - Suárez Quevedo, Diego (Anales de Historia del Arte, 2007)
It’s a valuation about the V Centenary of the death of Andrea Mantegna, the expositios during 2006, its catalogues and some publication because of this celebration, to conclude the importance of Leon Battista Alberti in the Mantova of the Gonzaga.